2021
DOI: 10.3389/fphar.2021.724405
|View full text |Cite
|
Sign up to set email alerts
|

Association Between SGLT2is and Cardiovascular and Respiratory Diseases: A Meta-Analysis of Large Trials

Abstract: The association between sodium-glucose cotransporter 2 inhibitors (SGLT2is) and various cardiovascular and respiratory diseases is unestablished. This meta-analysis aimed to explore whether use of SGLT2is is significantly associated with the occurrences of 80 types of cardiovascular diseases and 55 types of respiratory diseases. Large randomized trials of SGLT2is were included in analysis. Meta-analysis was conducted to synthesize risk ratio (RR) and 95% confidence interval (CI). Nine large trials were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
3
9
0
Order By: Relevance
“…33 Meta-analyses of SGLT2i cardiorenal trials found a reduced risk of non-infectious respiratory disorders, thus supporting findings by Au et al and our real-world study. [34][35][36] However, it can be difficult to distinguish the contribution of the reduced risk of heart failure-related hospitalization due to the known links between COPD and heart failure. 37 We observed a reduced hospitalization rate in some specific cancer types among SGLT2i initiators, for example, pancreas (C25) and bladder (C67) cancer.…”
Section: Discussionmentioning
confidence: 99%
“…33 Meta-analyses of SGLT2i cardiorenal trials found a reduced risk of non-infectious respiratory disorders, thus supporting findings by Au et al and our real-world study. [34][35][36] However, it can be difficult to distinguish the contribution of the reduced risk of heart failure-related hospitalization due to the known links between COPD and heart failure. 37 We observed a reduced hospitalization rate in some specific cancer types among SGLT2i initiators, for example, pancreas (C25) and bladder (C67) cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Some additional cardiovascular benefits obtained from SGLT2i use include blood pressure lowering effects of systolic and diastolic blood pressure [14,15]. A meta-analysis of nine large trials demonstrated that SGLT2i are associated with decreased incidence of nine types of cardiovascular disease and eleven types of respiratory disease [16]. The cardiovascular diseases with decreased incidences included conditions such as atrial fibrillation, bradycardia, hypertension, hypertensive emergency, acute cardiac failure, and varicose veins [16].…”
Section: Benefits and Risks On The Cardiovascular And Pulmonary Systemsmentioning
confidence: 99%
“…A meta-analysis of nine large trials demonstrated that SGLT2i are associated with decreased incidence of nine types of cardiovascular disease and eleven types of respiratory disease [16]. The cardiovascular diseases with decreased incidences included conditions such as atrial fibrillation, bradycardia, hypertension, hypertensive emergency, acute cardiac failure, and varicose veins [16]. The respiratory diseases associated with decreased incidence with SGLT inhibitor use included acute pulmonary edema, asthma, bronchitis, COPD, non-small cell lung cancer, pneumonia, pleural effusion, pulmonary edema and masses, respiratory tract infections, and sleep apnea syndrome [16].…”
Section: Benefits and Risks On The Cardiovascular And Pulmonary Systemsmentioning
confidence: 99%
“…Both syndromes seem to share an important role of extracellular matrix and immune infiltration by macrophages 8 . Interestingly, sodium–glucose cotransporter 2 (SGLT2) inhibitors have been associated with decreased risk of COPD in meta‐analyses including HF cohorts 9,10 . The effects of SGLT2 inhibitors may include improvement of myocardial efficiency and right filling pressures 11,12 mitochondrial function 13 and reduced inflammation, microvascular endothelial dysfunction, 14,15 oxidative stress, and fibrosis 16 …”
Section: Heart Failure With Preserved Ejection Fraction and Chronic O...mentioning
confidence: 99%